Efficacy of Non-Soy Isoflavone (Pueraria phaseoloides) on The Symptoms Severity Scoring by Kupperman Index in Menopausal Women - Made Tangkas; Widjajanto Ngartjono; Achmad Hidayat; Leny Silviana Farida (Asian Journal of Health Research, 2022)
Introduction: Menopause is defined by a decline in estrogen levels, which causes various symptoms. Treatments based on foods or supplements enriched in phytoestrogens, notably isoflavones, plant-derived compounds with estrogenic effects, have recently become quite popular. This study aims to see how effective non-soy isoflavone supplementation is for menopausal symptoms in women. Methods: 26 menopausal women were given 67.5 mg of non-soy isoflavone, and 25 menopausal women were given a placebo daily for 12 weeks in an analytical double-blind, randomized clinical trial (RCT). Inclusion criteria were (1) RCT, (2) perimenopausal or postmenopausal women experiencing menopausal symptoms, (3) intervention with an oral non-soy isoflavone. Symptoms Severity Score (SSS) based on the Kupperman index (KI) questionnaire was administered to the patients before starting and at the end of the study. The Statistical Package for Social Sciences (SPSS) software was used to analyze the responses. Results: The difference in SSS scores between the treatment and control groups was significant (p = 0.000). Women receiving 67.5 mg of non-soy isoflavone daily, reduced myalgia, fatigue, and hot flushes by 92.3%, 77%, and 53.8%, respectively. For clinical significance rating, relative risk reduction (RRR) is used. A significant RRR value resulted from myalgia symptoms (76.6%), fatigue (55.7%), hot flushes (39.2%), and SSS (68.7%). Conclusion: Isoflavones did not bring a significant change in Kupperman Index compared to placebo but provided significantly improved Symptoms Severity Scoring in menopausal women.